Application of ROMS-AGRIF over Levantine and Cyprus Seas - Nikolaidis, Andreas; Georgiou, Georgios; Hadjimitsis, Diofantos G.; Akylas, Evangelos (My University, 2019)
Abstract ROMS-AGRIF (Regional Ocean Model System, Adaptative Mesh Refinement In Fortran) is a free surface numerical ocean model that solves the primitive equation with the Boussinesq approximation with respect to hydrostatic vertical momentum balance. The model uses terrain-following vertical coordinates that allow differential stretching, within orthogonal, curvilinear, spherical horizontal coordinates. Equations are solved with short time steps for barotropic dynamic (ssh and 2D momentum) and a much larger time steps for baroclinic dynamic (T, S, 3D momentum) in a split explicit scheme. It uses rotated tensors to reduce diapycnal mixing and improved calculation of horizontal pressure gradient, following surface and bottom KPP turbulent closure model, thus obtaining high advection scheme. It uses adaptive mixed radiations/nudging open boundary conditions and it uses parallelization by two …
Keywords: ROMS-AGRIF; Cyprus Seas; Levantine; Regional Ocean Model System; Adaptative Mesh Refinement In Fortran; Spherical coordinates; Free surfaces; Seas